Usefulness of 18F-FDG PET/computed tomography in differentiating between subacute and chronic aortic dissection: initial investigation. Issue 7 (13th May 2022) - Higashigawa, Takatoshi; Ichikawa, Yasutaka; Chino, Shuji; Nakajima, Ken; Ouchi, Takafumi; Kato, Hiroaki; Hirano, Koji; Tokui, Toshiya; Kato, Noriyuki; Sakuma, Hajime
Abstract : Objectives: In the selection of thoracic endovascular repair for aortic dissection (AD), it is important to distinguish between the subacute and chronic phases, but there is no reliable way to distinguish between them in patients with unknown onset of AD. The purpose of this study was to assess the diagnostic performance of 2-[ 18 F] fluoro-2-deoxy-d -glucose ( 18 F-FDG)-PET/computed tomography (PET/CT) for discriminating subacute AD from chronic AD. Methods: Thirteen patients with AD who were medically treated and followed up for 6 months were studied. 18 F-FDG PET/CT images were obtained for each patient in the subacute phase (the first scan) and at 6 months (the second scan) after the onset. Target-to-background ratio (TBR) was measured as the maximum standardized uptake value (SUV) in the dissected aortic wall divided by blood pool SUV. Results: TBR was significantly higher in the first scan (mean ± SD, 1.97 ± 0.32) than in the second scan (1.69 ± 0.29, P  = 0.007). The area under the receiver operating characteristic curve of TBR for discriminating subacute AD from chronic AD was 0.76. With a threshold of 1.74, the TBR showed the sensitivity, specificity, and positive and negative predictive value of 85%, 69%, 73%, and 82%, respectively, for the discrimination of subacute AD from chronic AD. Conclusion: Metabolic assessment of dissected aortic wall by 18 F-FDG PET/CT is useful in differentiating between subacute and chronic AD and can provide important information in determining the appropriate indication for treatment for patients with AD of unknown onset.